Pengaruh Burnout, Motivasi Intrinsik, Work Life Balance Dan Kepuasan Kerja Terhadap Kinerja Perawat Pada Rumah Sakit Petala Bumi Pekanbaru - Deswarta; Hamanda Hadi Saputra; Insan Kamil Wahyudi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to determine and analyze how Burnout, Intrinsic Motivation, Work Life Balance and Job Satisfaction influence the Performance of nurses at Petala Bumi Hospital, Pekanbaru. The population in this study was 105 nurses with a sample of 52 nurses using the Slovin formula. Data collection techniques used questionnaires and interviews. The data analysis technique used in the Slovin formula study with a purposive sampling method. The research data was analyzed using multiple linear regression analysis. The results of the study showed that Burnout, Intrinsic Motivation, Work Life Balance and Job Satisfaction influenced the Performance of nurses at Petala Bumi Hospital, Pekanbaru